Ablation of the miR-465 Cluster Causes a Skewed Sex Ratio in Mice - Wang, Zhuqing; Meng, Nan; Wang, Yue; Zhou, Tong; Li, Musheng; Wang, Shawn; Chen, Sheng; Zheng, Huili; Kong, Shuangbo; Wang, Haibin; Yan, Wei (Frontiers in Endocrinology, 2022)
The X-linked miR-465 cluster is highly expressed in the testis, sperm, newborn ovary, and blastocysts as well as in 8-16 cell embryos. However, the physiological role of the miR-465 cluster is still largely unknown. This study aims to dissect the role of the miR-465 cluster in murine development. Despite abundant expression in the testis, ablation of the miR-465 miRNA cluster using CRISPR-Cas9 did not cause infertility. Instead, a skewed sex ratio biased toward males (60% males) was observed among miR-465 KO mice. Further analyses revealed that the female conceptuses selectively degenerated as early as embryonic day 8.5 (E8.5). Small RNA deep sequencing, qPCR, and in situ hybridization analyses revealed that the miRNAs encoded by the miR-465 cluster were mainly localized to the extraembryonic tissue/developing placenta. RNA-seq analyses identified altered mRNA transcriptome characterized by the dysregulation of numerous critical placental genes, e.g., Alkbh1, in the KO conceptuses at E7.5. Taken together, this study showed that the miR-465 cluster is required for normal female placental development, and ablation of the miR-465 cluster leads to a skewed sex ratio with more males ( 60%) due to selective degeneration and resorption of the female conceptuses.